MERANGKUL KEBERAGAMAN STOP PERUNDUNGAN: PROGRAM PENGABDIAN MASYARAKAT DI SMP NEGERI 6 YOGYAKARTA - Daniel Jesayanto Jaya; Aprilianata; Yanuar Khaldun; Aulya Sani; Fenny Herlinda Walu Wanja; Modjo Kale Djami; Candra Sihura; Mughnil Muhtaj; Inayah Wulandari; Yuleks Jurumudi; Lutfi Marfuah; Sahra (Wisesa: Jurnal Pengabdian Masyarakat, 2025)
Bullying in schools remains a serious issue in Indonesia, threatening adolescents’ psychological well-being. A lack of tolerance and empathy contributes to conflicts and bullying among students. The “Awardee Mengabdi” community service program by LPDP UNY cohort 11.0 was implemented under the theme “Embracing Diversity, Stopping Bullying.” This program, in the form of an interactive seminar and group discussions, aimed to increase junior high school students’ awareness of the importance of tolerance, empathy, healthy communication, and bullying prevention. The methods included expert lectures, interactive ice-breaking games, group case discussions, and the formation of anti-bullying commitments. The results show that 60 participating students were highly enthusiastic and actively engaged in Q&A and discussions. Their knowledge of various forms of bullying and its impacts improved, as reflected in their enhanced ability to identify bullying cases and propose prevention steps. Teachers and parents observed positive changes in students’ attitudes after the program, such as greater respect for diversity and courage to say no to bullying. In conclusion, the program achieved its goal of fostering a culture of tolerance and anti-bullying at school. It is recommended that continuous collaboration among schools, students, and stakeholders be carried out to ensure the program’s sustainable impact.